A Clinical Study about the Frequency of Physiological Skin Changes Observed in Pregnant Females - Mariam Sheikh, Ambreen Mumtaz, Nosheen Salahuddin, Qurat-Ul-Aian Munir, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find out the frequency of physiological skin changes in pregnant females. Methods: In this descriptive cross-sectional study, 100 pregnant females presenting in outpatient departments of dermatology & gynaecology, obstetrics at Akhtar Saeed Trust Hospital Lahore were enrolled over a period of 1year from June 2020 till June 2021. All consenting pregnant females were enrolled in this study and pregnant females with pre-existing skin diseases and having specific dermatosis of pregnancy were excluded from this study. Detailed history was taken & their complete physical & dermatological examination was carried out and the findings were noted down in pre-designed performa. Results: Physiological skin changes were observed in all the patients in our study. The agr range of patients in this study was 18-35 years, the mean age being 25.06 years. The most common cutaneous manifestation observed was hyperpigmentation out of which linea nigra was commonest finding present in 92% of patients, hyperpigmentation on various parts of body in 16 %, melasma in 12% of patients and 76% of patients showed vascular changes. Practical Implications: The rationale of this study is to assess the frequency of physiological changes occurring in pregnant females. So that they can be promptly and correctly diagnosed and thus reducing the emotional and financial stress on community. Conclusion: Pregnant females suffer from a variety of physiological skin changes. Awareness & recognition of these changes will help in timely diagnosis and treatment. Keywords: Pregnancy, skin physiological changes, hyperpigmentation, melasma, vascular changes